Participatory Sound Art Technologies, Aesthetics, Politics - Keylin, Vadim (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
"How exactly can listeners participate in sound art? Vadim Keylin explores this issue within contemporary aesthetics through an impressive series of analyses, through fieldwork, conceptual critique as well as through reflections on epistemologies, art history and media history. He proposes to conceptualize participatory sound art through a sonic pragmatism that suggests a stimulating interpretation and application of the notion of affordances in the field of sound studies. With Keylin's approach, works of sound art become consistently recognizable as scenarios for and of encounters." -Holger Schulze, Professor of Musicology, Copenhagen University, Denmark "It is always good to read how young, promising scholars contribute new insights to the prevailing sound studies discourse. Vadim Keylin's Participatory Sound Art opens a field, a niche, within sound studies that so far hasn't been explored systematically, namely the relationship between sound art and participatory art, thereby emphasizing sound art as a participatory art. Reflecting on many interesting sound artworks and bringing them into contact with theories grounded in pragmatism, Keylin has managed to enrich the already impressive theories on sound art with new concepts, new perceptions, and new approaches." -Marcel Cobussen, Professor of Auditory Culture, Leiden University, The Netherlands This book addresses a major gap in sound art scholarship: the role of audience participation. It offers a survey of participatory sound art from its origins in the historical avant-gardes to the non-institutionalized forms of sonic creativity in contemporary digital culture. In doing so, it proposes an innovative theoretical framework for analysing such phenomena, rooted in Pragmatist aesthetics, affordance theory and postcritique. Combining artwork analyses with qualitative studies, this book contributes to the growing fields of sound studies and participation studies, as well as to curatorial practice regarding sound art and participatory art. Vadim Keylin holds a PhD in Aesthetics and Culture from Aarhus University and is currently a research associate in the ERC project "Poetry in the Digital Age" (University of Hamburg). He has published peer-reviewed articles and book chapters on experimental musical instruments, interactive sound art and sound in participatory culture.
Chapter 1: Introduction -- Chapter 2. Histories -- Chapter 3. Discourses -- Chapter 4. Affordances -- Chapter 5. Perspectives -- Chapter 6. Gestures -- Chapter 7. Conclusion.
Keywords: Science -- Social aspects; Mass media and culture; Music; Sound Studies; Media Culture; Music; Science and Technology Studies